2010
DOI: 10.1093/bioinformatics/btq186
|View full text |Cite
|
Sign up to set email alerts
|

TEAM: efficient two-locus epistasis tests in human genome-wide association study

Abstract: As a promising tool for identifying genetic markers underlying phenotypic differences, genome-wide association study (GWAS) has been extensively investigated in recent years. In GWAS, detecting epistasis (or gene–gene interaction) is preferable over single locus study since many diseases are known to be complex traits. A brute force search is infeasible for epistasis detection in the genome-wide scale because of the intensive computational burden. Existing epistasis detection algorithms are designed for datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 26 publications
0
114
0
1
Order By: Relevance
“…The genetic interaction network is con- Figure 8: Protein-protein interaction network, gene coexpression network, genetic interaction network and crossdomain relationships structed using a large-scale Hypertension genetic data [10], which contains 490032 genetic markers across 4890 (1952 disease and 2938 healthy) samples. We use 1 million top-ranked genetic markerpairs to construct the network and the test statistics are used as the weights on the edges between markers [36]. The constructed heterogenous networks are shown in Fig.…”
Section: Protein Module Detection By Integrating Multi-domain Heterogmentioning
confidence: 99%
“…The genetic interaction network is con- Figure 8: Protein-protein interaction network, gene coexpression network, genetic interaction network and crossdomain relationships structed using a large-scale Hypertension genetic data [10], which contains 490032 genetic markers across 4890 (1952 disease and 2938 healthy) samples. We use 1 million top-ranked genetic markerpairs to construct the network and the test statistics are used as the weights on the edges between markers [36]. The constructed heterogenous networks are shown in Fig.…”
Section: Protein Module Detection By Integrating Multi-domain Heterogmentioning
confidence: 99%
“…Among the methods that directly test for statistical epistasis, we report TEAM (Zhang et al 2010a) and FastEpistasis (Schüpbach et al 2010). The authors of FastCHI (Zhang et al 2009), FastANOVA (Zhang et al 2008), COE (Zhang et al 2010b) and TEAM presented a review in which TEAM was reported as the most appropriate for handling human data sets, and was therefore chosen to represent the family of methods.…”
Section: Computational Savings From Group Samplingmentioning
confidence: 99%
“…We then compute the difference in the average trait value between the two groups to determine whether the pair of SNPs is significantly associated with the trait. Finding an association between a trait and a pair of SNPs is called the ''pairwise association test,'' and recently, several different methods have been proposed for pairwise association tests (Evans et al, 2006;Zhang et al, 2010;Prabhu and Pe'er, 2012;Yang et al, 2009;Millstein et al, 2006;Ljungberg et al, 2004).…”
Section: Introduction Gmentioning
confidence: 99%
“…Most of these methods are only applicable to case/control data. These methods include TEAM (Zhang et al, 2010), which uses a dynamic programming approach to identify significant pairs, SIXPAC (Prabhu and Pe'er, 2012), which utilizes a novel randomization technique, BOOST (Wan et al, 2010), which utilizes a Boolean representation of data and a screening stage to filter out most nonsignificant SNP interactions, and RAPID (Brinza et al, 2010), which utilizes geometric properties of the v 2 statistic to identify significant pairs. However, none of these methods are applicable to quantitative traits.…”
Section: Introduction Gmentioning
confidence: 99%